Shake and Shiver stories facts puzzles poems fun! - "Abney Louise"; Gavin Bishop; Shortland Publications (Auckland, New Zealand Shortland Publications, 2004)
A compilation aimed at young readers, combining imaginative stories, intriguing facts, engaging puzzles, and delightful poems to foster a love for reading and learning.
Includes a variety of content such as short stories, factual snippets, puzzles, and poems designed to entertain and educate young readers. Illustrations enhance the textual content, providing visual engagement for children.
Keywords: Children's literature, Puzzles, Poetry, Short stories